(untitled) (Quality Advancement in Nursing Education - Avancées en formation infirmière, 2022)
Practice-based, or workplace-integrated, learning is a fundamental component of Baccalaureate of Science in Nursing (BSN) programs. The Dedicated Education Unit (DEU) model has been implemented widely in a range of contexts over the past two decades as an alternative to traditional faculty-led and preceptorship models. In Victoria, British Columbia, academic and practice nursing partners adapted and piloted the DEU in 2003 as a Collaborative Learning Unit (CLU) model. As with other DEU initiatives/innovations, the CLU was proposed primarily as a solution to increasing demands on student placement capacity and reduced preceptor availability. Over the past 17 years the CLU approach has been expanded to the point where over 85% of BSN students now complete their final practice courses within this model. As part of a larger program of study evaluating the CLU model, we employed Bowen’s document analysis methodology to explore the unique contextual issues that shaped development of this model and to critically reflect on historical and political influences on expansion and sustainability. We located printed and electronic documents developed by academic-practice partner teams from the time of early interest about the model in 2001 to 2020. Data were extracted about authorship, purpose, process and key recommendations, in particular related to the characteristics and processes of CLUs that supported development, implementation, and sustainability. Supplementary strategic documents were also reviewed for provincial health system, national nursing, and nursing education contexts. Overall, we noted a pattern of substantial initial collaboration, investment and expansion, leading to the CLU model becoming established practice for the majority of senior practice placements. However, multiple economic and system influences across healthcare and post-secondary education sectors contributed to a gradual reduction in infrastructure during the past ten years. We suggest that limited intentional focus on sustainability in and between academic and healthcare organizational contexts over time contributed to some erosion of nursing education infrastructure and potentially dilution of the positive impact of this practice education model. Despite these challenges, student placement data patterns in Victoria indicate that without the CLU model, it would be significantly more challenging to return to relying on the preceptorship model for senior practice education courses, particularly as many of the initial contextual factors endure.